Síndrome del impostor (Assemble You, 2022)
Welcome to Audio Learning by Assemble You. One of the most popular and least discussed topics in offices around the world is Impostor Syndrome. However, we often think we are alone when we doubt ourselves because no one else expresses their own doubts. However, the reality is that this is what everyone else is doing too! It is an effect called pluralistic ignorance. In this content we review what it is, how common it is, how some of the most successful people in the world live with it, and how to manage it in a healthy way. Learning Objectives Learn what Imposter Syndrome is and how popular it is Learn actionable techniques to limit the negative effects of Imposter Syndrome.